Histories of ornament from global to local - Necipoglu, Gulru; Payne, Alina (Princeton, New Jersey Princeton University Press, 2016)
"This lavishly illustrated volume is the first major global history of ornament from the middle ages to today. Crossing historical and geographical boundaries in unprecedented ways and considering the role of ornament in both art and architecture, Histories of Ornament offers a nuanced examination with their Islamic, Indian, Chinese and Mesoamerican counterparts. At a time when ornament has re-emerged in architectural practice and is a topic of growing interest to art and architectural historians, the book reveals how the long history of ornament illuminates its global resurgence today." -- Provided by publisher
Chapter 1 Ornament and its users: from the Vitruvian tradition to the digital age -- Chapter 2 A natural history of ornament -- Chapter 3 Inscription: On the surface of exchange between writing, ornament, and tectonic in contemporary architecture -- Chapter 4 Ornament as weapon: ballistics, politics, and architectural adornment in Semper's treatise on ancient projectiles -- Chapter 5 The passage of the other: elements for a redefinition of ornament -- Chapter 6 The invention of Mudejar art and the viceregal aesthetic paradox: notes on the reception of Iberian ornament in New Spain -- Chapter 7 The flaw in the carpet:disjunctive continuities and Riegl's arabesque -- Chapter 8 Vesting walls, displaying structure, crossing cultures: transmedial and transmaterial dynamics of ornament -- Chapter 9 Gothic-framed byzantine icons: Italianate ornament in the Levant during the late middle ages -- Chapter 10 Timurid architectural revetment in Central Asia, 1370-1430: The Mimeticism of mosaic Faience -- Chapter 11 Early modern floral: the agency of ornament in Ottoman and Safavid visual cultures -- Chapter 12 Ornamental defacement and protestant iconoclasm --Chapter 13 Migration of techniques: inlaid marble floral decoration in baroque Naples -- Chapter 14 Innovation, appropriation, and representation: Mughal architectural ornament in the eighteenth century -- Chapter 15 Ornament, form, and vision in ceramics from medieval Iran: relfections of the human image -- Chapter 16 Variety and metamorphosis: form and meaning in the ornament of Amico Aspertini -- Chapter 17 Images as objects: the problem of figural ornament in eighteenth-century France -- Chapter 18 Ornament and vice: the foreign, the mobile, and the Cocharelli fragments -- Chapter 19 GIlded bodies and brilliant walls: ornament in America before and after the European conquest -- Chapter 20 The poetics of portability -- Chapter 21 "This is Babel": Sicily, the Mediterranean islands, and Southern Italy (1450-1550) -- Chapter 22 Wrapped in fabric: Florentine facades, Mediterranean textiles, and a-tectonic ornament in the renaissance -- Chapter 23 Threads of ornament in the style world of the fifteenth and sixteenth centuries -- Chapter 24 The currency of ornament: machine-lathed anticounterfeiting patterns and the portability of value -- Chapter 25 Grammars of ornament: dematerialization and embodiment from Owen Jones to Paul Klee -- Chapter 26 Sober ornament: Materiality and luxury in German modern architecture and design
Includes bibliographical references (pages 411-444) and index.
Keywords: Decoration and ornament, Architectural; Decoration and ornament, Architectural -- History